2016
DOI: 10.3109/07420528.2016.1143480
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor artificial light at night, obesity, and sleep health: Cross-sectional analysis in the KoGES study

Abstract: Obesity is a common disorder with many complications. Although chronodisruption plays a role in obesity, few epidemiological studies have investigated the association between artificial light at night (ALAN) and obesity. Since sleep health is related to both obesity and ALAN, we investigated the association between outdoor ALAN and obesity after adjusting for sleep health. We also investigated the association between outdoor ALAN and sleep health. This cross-sectional survey included 8526 adults, 39-70 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 69 publications
3
97
0
Order By: Relevance
“…However, the proper timing of exercise and its potential added benefit of improving circadian entrainment have not been investigated thoroughly. Disruption of circadian rhythms (e.g., by shift work, social jetlag, early-morning schedules) is associated with metabolic disorders, cardiovascular disease, and cancer (6)(7)(8)(9)(10)(11). If exercise could reduce circadian disruption, then it may also improve the risk factors associated with this disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proper timing of exercise and its potential added benefit of improving circadian entrainment have not been investigated thoroughly. Disruption of circadian rhythms (e.g., by shift work, social jetlag, early-morning schedules) is associated with metabolic disorders, cardiovascular disease, and cancer (6)(7)(8)(9)(10)(11). If exercise could reduce circadian disruption, then it may also improve the risk factors associated with this disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that circadian disruption is a health risk. Shift work chronically disrupts the circadian system and is also associated with increased risk of cancer, obesity, and cardiovascular disease (6)(7)(8)(9)(10)(11). Nonshift workers also experience chronic forms of circadian disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exposure to bright artificial light in the evening before bedtime has been associated with a delay in circadian phase, as assessed by measures of subjective chronotype (Martin et al 2012; Vollmer et al 2012), subjective sleep timing (Koo et al 2016), salivary melatonin levels (Gordijn et al 1999; Benloucif et al 2008; Cajochen et al 2011) and core body temperature (Krauchi et al 1997). Furthermore, adolescents living in urban areas and exposed to bright artificial light at night have a later chronotype as assessed by the Munich ChronoType Questionnaire (MCTQ) and Morningness–Eveningness Questionnaire (MEQ), compared to those living in more rural settings (Vollmer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which outdoor lighting impacts human health is yet to be reliably determined. While epidemiological studies have found correlations between the amount of outdoor lighting and some health effects (Kloog, Haim, Stevens, Barchana, & Portnov, 2008;Koo et al, 2016), as with ecological patterns, they are limited Sensitivities to white light were calculated from experimentally derived values in existing literature (B atnes et al, 2013;Crisp & Ritz, 1973;Forward, Cronin, & Stearns, 1984;Gorbunov & Falkowski, 2002;Svane & Dolmer, 1995;Tankersley, Mckelvey, & Forward, 1995;Young & Chia, 1982) DAVIES AND SMYTH | 877 by the inferences that can be drawn from satellite images (Defence Meteorological Satellite Programme Operational Line Scan) with insufficient spatial resolution (5 km) to differentiate exposure to ALAN from other factors that covary across city districts at fine spatial scales (Elvidge et al, 2007;Kyba, 2016). The need for higher resolution images or novel approaches that can disentangle the effects on both ecology and human health of multiple urban pollutants that covary is clear, although individual-level sensors can also reveal important impacts of daily light exposure on circadian disruption and stress (Figueiro et al, 2017).…”
Section: Impacts On Human Healthmentioning
confidence: 99%